Citizenship competence in the Paraguayan educational system. A look from secondary education - Castillo-Vega, Jose (2023)
The present investigation sought to describe the approach to citizen competence in secondary education of the Paraguayan educational system, in order to determine its contribution in the formation of young people, who must participate in a critical, constructive and reflective way in the society that experiences a weak democracy. The study is approached from documentary research, with a qualitative descriptive approach. The findings show that, although citizenship competencies are present in the curriculum, the ways of addressing it in the study programs are not specifically established, as well as, it is inferred that they can be identified as an exclusive requirement for the disciplines of the Social Sciences and not so for the other disciplines that are part of the academic component. The role of teachers is also identified as a weak link, so it is necessary to prioritize teacher training and research on classroom practices. On the other hand, the creation and recognition of student centers at the national level is identified as a strength, since these constitute a space for training and citizen participation. Finally, it highlights that democratic training is not only a commitment of the educational system but must be recognized as a responsibility shared with society, especially the family, which is the first school for students and the central nucleus where the courses must be taught. ethical and democratic values.